Histological and Comparative Transcriptome Analyses Provide Insights Into the Immune Response in Pearl Sac Formation of Hyriopsis cumingii - Shen, Wenying; Hu, Yiwei; He, Zhengkai; Xu, Shuting; Xu, Xinyue; Zhang, Genfang; Ren, Gang (Frontiers in Marine Science, 2020)
Immune response plays an important role in the pearl sac formation and pearl quality. However, there is little knowledge about the mode and mechanism of the immune responses in the pearl sac formation of H. cumingii, which produced the largest production of non-nucleated freshwater pearl in China. In this study, we monitored the process of pearl sac formation by histology examination for 18 days after grafting. The results showed that a large number of hemocytes aggregated in the pearl sac cavity on day 8 after grafting and provided organic substrate for the deposition of extracellular matrix and CaCO3 crystal and mediated the initiation of pearl forming on day 12. These results revealed the important role of hemocytes on the early pearl sac and pearl formations. In the transcriptome analysis of pearl sac at the key time points of day 0 and day 6, 8, 12 after grafting, the expression profiles of the immune-related genes revealed the immune response pattern of H. cumingii after grafting. The significant up-regulation of the hydrolytic enzymes, acute phase proteins, and antimicrobial peptides of humoral defense factors on day 6 after grafting suggested that these immune-related gene products were the main immune defense during the early wound healing; Meanwhile, the continuous up-regulation of antioxidant enzymes such as Cu-Zn SOD, Se-GPX, and tyrosinase in prophenoloxidase (proPO) system on day 8 and day 12 suggested the important role of these immune effectors in oxidation-reduction on the later stage of pearl sac and pearl formations in H. cumingii. Moreover, the results of KEGG analysis of differentially expressed genes suggested the potential regulatory function of the signaling pathways of proPO system and complement system during pearl sac formation. These results provided valuable new insights into the roles and functions of the immune system in pearl sac and pearl formation.